Diazepam Inhibits Proliferation of Lymph Node Cells Isolated from Rats with Experimental Autoimmune Encephalomyelitis - Fernández Hurst, Nicolás (2014)
Objective: Experimental autoimmune encephalomyelitis (EAE) is an inflammatory demyelinating disease with similar-ities to human multiple sclerosis involving peripheral activa-tion of autoreactive T cells which infiltrate the central ner-vous system and react to self antigens leading to damage. In previous studies, we have demonstrated that treatment with diazepam decreases the incidence and histological signs as-sociated with the disease and diminishes immunological re-sponses. The aim of the present work was to evaluate direct effects of diazepam on isolated T cells involved in immune responses during the development of EAE. Methods: Ani-mals were sensitized with whole myelin to induce EAE and sacrificed during the acute phase of the disease. In mono-nuclear cells isolated from popliteal lymph nodes, cell viabil-ity, apoptosis induction, proliferation and cytokine produc-tion were evaluated. Results: Diazepam did not have a toxic or proapoptotic effect on the cells, at least up to the concen-tration of 25 μ M , but proliferation, CD8+ T-cell activation and proinflammatory cytokine production were dose-depend-ently decreased. Conclusions: Diazepam has a direct inhibi-tory effect on the proliferation and activation of T lympho-cytes isolated from the main lymphoid organ involved in disease onset and this could be one of the mechanisms that contribute to the beneficial effect previously observed with diazepam in vivo during EAE development.